The effect of error correction types on grammatical accuracy in student essay revision - Al Saeed, Neveen Saeed Abd Al Kareem (AUC Knowledge Fountain, 2010)
There has been an on-going debate on whether error feedback helps students to improve their grammatical accuracy from one draft to the other (Ferris, 1999; Truscott, 1996; 1999). Some studies found that error correction was effective (Ferris & Roberts, 2001) and others refuted this argument (Semke, 1984; Kepner, 1990). Their findings showed that feedback had no or non-significant effects on accuracy. According to previous research, one area which has not been properly studied is a comparison between groups receiving feedback and a no feedback group. Therefore, the present study investigated the effect of feedback on grammatical accuracy by comparing three types of feedback: errors coded, errors underlined, and no grammar feedback. The instruments included a pretest, a posttest and two treatments. Participants were first- year students in the English Literature and Language Department at Ain Shams University. Means and standard deviations were calculated. ANOVA and dependent t-tests were also used to analyze the data. Data analysis revealed no significant differences in the improvement of grammatical accuracy in the two treatment groups. It was however found that both treatment groups outperformed the no-feedback group in editing verb and noun-related errors. However, the control group outperformed the two other groups in correcting their article-related errors. The researcher concluded that even if students do not receive grammar feedback, their writing improves because of the rewriting process itself.